Ocena kakovosti življenja bolnika s kronično obstruktivno pljučno boleznijo - Škrgat-Kristan, Sabina (Obzornik zdravstvene nege, 2009)
Introduction: Chronic obstructive pulmonary disease (COPD) has a detrimental effect on the performance of daily activities and consequently on health-relaCed quality of life (HRQOL). Different HRQOL instruments have been developed to quantify the impact of COPD on a patient's daily life, and are used in clinical trials to measure the changes in HRQOL. One of these instruments is the St. George's Respiratory Questionnaire (SGRQ). The basic purpose of this research is to compare HRQOL between patients on home long-term oxygen treatment (h-LTOT) and COPD patients who do not need such treatment yet. The study determines the correlation between the results of theSGRQ, the six-minute walk test and lung function parameters. Methods: All participating patients were examined at the University Clinic of Respiratory and Allergic Diseases Golnik. The examination included a pulmonary function test, a six-minute walk test and the SGRQ. Results: Patients on h-LTOT can walk 159 m less than patients without h-LTOT, and their average forced expiratory volume in 1 second (FEV I ) is 800 while FEV 1 of patients without h-LTOT is 1600. The total SGRQ assessment is higher by 28% which means a lowerquality of Iife. The biggest difference in the assessment of SGRQ categories appeared in the subgroup dealing with activities. The comparison ofthe assessment of the quality of life and of pulmonary function shows that the correlation between the two is counter proportionate. The lower the pulmonary function, the lower the assessment of the quality of life. The strongest correlation is that between the distance that patients can walk and the SGRQ assessment: the lesser the distance they can walk, the higher is their % in SGRQ, which means a lower quality of life. % FEV 1 moderately correlates with the distance the patients can walk; the higher it is, the greater the distance patients can walk. (Abstract truncated at 2000 characters)
Keywords: ankete; bolniki; kronična obstruktivna pljučna bolezen; Kvaliteta življenja; Lung Diseases, Obstructive; Lung Volume Measurements; pljučne bolezni; Pljučne bolezni obstruktivne; Pljučni volumen, meritve; Quality Of Life; Questionnaires